Distance Education as a New Approach to Education in Iran: An investigation on the effectiveness of distance education centers and their curriculum at high school level in the academic year 2005-2006 across the country - Mohsen Talebzadeh; Seyyed-Ali Hosseini (فصلنامه نوآوری‌های آموزشی, 2007)
The aim of this study is to investigate the effectiveness of distance education activities as one of the new educational methods and approaches in the country, which are implemented and directed by the institute of Distance Education of the Ministry of Education. The effectiveness of education activities of this method is based the approvals of the institute for reaching distance education goals. These goals include enhancing flexibility in instructional methods, the impact of technology on the method of education offering, the degree of students self – reliance and self – study, and the aim of assessing implementation of guidelines. In order to do so, a survey questionnaire consisting of 35 questions were presented to a sample of 290 principals and tutors of distance education centers at the high school level across the country.